Eficiência de herbicidas no controle de plantas daninhas latifoliadas em mamona - Vitorino, H.s. [UNESP] (2012)
The objective of this study was to evaluate the effectiveness of different herbicides, applied in direct spray, to control dicotyledonous weeds in castor beans. The herbicides tested were saflufenacil (28, 40 and 56 g ha-1), carfentrazone-ethyl (30 g ha-1), flumioxazin (25 g ha-1), glyphosate (720 g ha-1) and glyphosate + saflufenacil (720 + 28 g ha-1) applied post-emergence on three species of weeds (Richardia brasiliensis, Sida rhombifolia and Ipomoea grandifolia), and a control without herbicide. The herbicides were sprayed when the castor bean plants showed 50 to 70 cm of height. Visual assessments of the degree of control were performed at 3, 7, 14, 21 and 28 days after treatment application. The study was installed in a randomized complete block design with three replications. The herbicide saflufenacil was effective in the control of all the weeds studied, and the herbicides carfentrazone-ethyl and flumioxazin presented only satisfactory control of weeds. The mixture tested was effective in the control of all weeds.